The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3991/ijim.v17i09.38663
|View full text |Cite
|
Sign up to set email alerts
|

Combination of M-learning with Problem Based Learning: Teaching Activities for Mathematics Teachers

Abstract: This study was conducted to identify elements (teaching activities) that teachers can engage with involving a combination of M-learning methods with Problem-Based Learning methods (M-PBL). This study was conducted using the Nominal Group Technique (NGT) involving 11 experts with various fields of expertise such as mathematics education, educational technology, M-learning, pedagogy and the curriculum as well as primary school mathematics education teachers. The analysis of the findings was carried out using des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Apart from students' learning abilities, flipped classroom, PBL, and mobile learning have been tested by many researchers and have had a positive effect on student learning activities. Zakaria et al [23], noted that information sharing activities are increasing. Chiang dan Wu [24] wrote that students' collaborative learning activities were increasing; Hwang dan Chen [25] concluded that student performance and students' interactive patterns had increased.…”
Section: Research Resultsmentioning
confidence: 99%
“…Apart from students' learning abilities, flipped classroom, PBL, and mobile learning have been tested by many researchers and have had a positive effect on student learning activities. Zakaria et al [23], noted that information sharing activities are increasing. Chiang dan Wu [24] wrote that students' collaborative learning activities were increasing; Hwang dan Chen [25] concluded that student performance and students' interactive patterns had increased.…”
Section: Research Resultsmentioning
confidence: 99%